Analisis Kesulitan Pembelajaran Berdiferensiasi pada Materi Bagian Tubuh Tumbuhan di Sekolah Dasar - Iin Fitriah; Aan Widiyono (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to determine differentiated learning difficulties among primary school students. This condition is caused by teachers and students having difficulty implementing differentiated learning. This research design uses qualitative research. The research subjects were 24 students of class IV of SDN 3 Menganti. Data collection uses observation and interviews. Data analysis uses data reduction, data presentation and conclusion. Test data validity using technical triangulation and source triangulation. The results of this research show that teachers find it difficult to bring together the abilities and learning styles of each student and that the time, facilities and materials that teachers need to prepare are limited. The problems are also found among the students themselves, particularly due to internal and external factors. By preparing learning plans, developing learning strategies, learning materials, and performing cognitive diagnostic assessments that aim to maximize time allocation during the learning process